A review and exploration of the effects of university-company cooperation policy on innovation outputs in the Brazilian industry - Liu, Boyu (2019)
The importance of cooperation between universities and firms has been drawing attention in the academic field. The relationship among university, government and firms is the key point in promoting innovation. Brazil, as one of the most influential countries in the southern hemisphere, has implemented measures and policies in promoting technology and innovation. These policies were born towards increasing productions, exports, investment and employment and have been playing important roles in developing innovation. Among them, Technological Innovation Law (Law No.10, 973/04) launched in 2004 is considered one of the most important policies in the Brazilian National Innovation System. This law stipulates the rules from the national level for the researchers from universities and research institutes participating in research projects with companies. In order to create technological autonomy and industrial development in Brazil, this law establishes measures for innovation within companies and universities. With the aim to analyze whether the innovation policy from the government will affect the cooperation and improve innovation outputs in the Brazilian industry, this research uses data from the Technological Innovation Research (Pesquisa de Inovação Tecnológica, PINTEC) and puts forward four hypotheses. By analyzing the data of the university-company cooperation and using multiple regression model and mediator model, the results will show whether the policy is effective and could promote innovation outcomes for the companies.